Ergodic Structural Diversity Predicts Dynamics in Amorphous Materials - Yang, Zeng-Yu; Wang, Yun-Jiang (Frontiers in Materials, 2022)
Identification of the flexible local environments from a disordered medium has been a long-standing challenge. Here, we introduce a time-relevant structural Shannon entropy as a unique feature of the atomic-scale environment in glass, which is based on a metric of the time-invariant, or ergodic, Voronoi structural diversity that an atom experiences during sufficiently long-time thermal fluctuation. This new concept of time-relevant Shannon entropy simultaneously integrates the static topology and the vibrational feature such that it potentially probes all the possible configurational space in a sub-basin of the local potential energy landscape. This structural representation is not only capable of predicting the energy barrier of the elementary structural excitation, but also demonstrates a robust correlation with boson peak in metallic glasses although the physical entity is defined from purely structural aspect. The proposition therefore represents a successful demonstration of the physics-informed structure--property relationship in amorphous materials.